The Deixin in Class VII Indonesian Language at SMP Negeri 7 Seluma For The 2023 Academic Year. - Fanhari, Muhammad Fauzan; Rahayu, Ngudining; Wardhana, Dian Eka Candra (UNIB Press, 2025)
The focus of this research is the application of deixis by teachers and students of class VII SMP Negeri 7 Seluma in interactions learning Indonesian. The research method used is a descriptive method with data collection techniques namely observation techniques, note-taking techniques and recording techniques. The collected data is processed using 5 steps, namely 1) Data transcription; 2) Data identification; 3) Data classification; 4) Data interpretation; and 5) Conclusion. The results of the research found 3 types of deixis, namely personal deixis which is divided into three parts, including: singular first person deixis with the characteristic